The effects of breastfeeding position and the change in nutritional habit on infantile colic: A randomized clinical trial - Sadeghzadeh Fard Sorkhabi, Sara; Kazemian, Mohammad; Shamshiri, Ahmad Reza (Researcher Bulletin of Medical Sciences, 2022)
Purpose: This study aimed to investigate the role of non-pharmacological method of breastfeeding and maternal nutrition in the treatment of infantile colic in order to reduce the role of pharmacological method. Methods: This study was a double-blinded clinical trial study on 62 infants less than 4 months of age referred to Emergency ward of Mofid Hospital in 2014. The infants were randomly divided into two groups that one group received routine colic treatment without any intervention (as the control group) and the other group received hypoallergenic lactation and also were trained on how to breastfeed appropriately. On the second and tenth days, all mothers were contacted and the duration of crying and restlessness of the infant was assessed. Results: The severity of colic significantly lower in intervention group as compared to control group on the second and tenth days of intervention. In this regard, the mean change in severity of colic at the end of assessment was 2.4 ± 2.2 in intervention group and 0.7 ± 1.5 in control group (p < 0.001). The mean change in colic intensity in subgroups with complete, partial and low adherence was 4.1 ± 2.4, 2.5 ± 1.6, and 0.2 ± 1.6 respectively indicating a significant difference (p < 0.001). Conclusion: Comprehensive mothers' training on how to breastfeed and determine the best breastfeeding position along with the change in nutritional habit can significantly reduce colic severity.